The storybook: powerful dynamizer of reading. (Journal of Parents and Teachers, 2014)
It is essential for children to read, and to do this, we have to instill interest in reading. This article presents several activities to be carried out in classrooms from books as motivating elements and animation to reading. In addition, guidelines are provided to guide families in the field of reading.
Keywords: Reading; books; stories; animation; motivation; games; activities; orientations for the family.